On Some Features of Logical Thought in Writing - Karapetyan, Marina (Armenian Folia Anglistika, 2016)
This paper considers some features of logical thinking in persuasive essay writing. A solid essay is logically organized and well-developed; it advances consistent arguments supported by strong evidence. At the same time, it demonstrates cogency of reasoning, completeness and unity of thought. All this suggests that the ideas in each paragraph and the overall essay relate to one another, are arranged in a logical sequence and lead to a valid conclusion. Based on scientific approach to logical reasoning, the paper outlines various reasoning techniques that can be employed to produce a forceful essay.
Keywords: logical sequence; deduction; induction; analogy; causal argument; predictions; credibility